Étude multifacultaire de la qualité des lampes à polymériser utilisées au Liban - Roula BERBARI; Rola EL-ZEIN; Georges ABI HATEM; Samia ABOU JAOUDÉ; Elia SFEIR; Mounir DOUMIT (International Arab Journal of Dentistry (IAJD), 2016)
The objective of the present study is to evaluate the quality of dental curing lights mainly the light emitting diode (LED) and Halogen lights used by dentists in their private practice and by students in three dental schools in Lebanon. The effectiveness of 318 curing lights was evaluated. The type, intensity and age of equipment were evaluated at an interval of two years. All the tested devices were effective and recent. The LED lights were the most used. A difference in the intensities of the dental curing light was observed between the three faculties.